Portraying the English Extensive Program in an Indonesian Islamic Institution: A Case Study - Azizah, Shofiah Nur; Pratiwi, Dwiyani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This case study portrays the implementation of the English extensive program in Central Language Improvement (CLI) of an Indonesian Islamic Institution, English teacher’s strategies, and students’ perceptions of the program. The data were collected from the principal, a CLI member, an English teacher, and three students who won English competitions through observations, interviews, and documents analysis. The data were analyzed qualitatively using the framework proposed by Miles et al. (2014). The study shows several main findings: (1) the CLI is run by students with the principal and English teachers’ support, (2) the CLI contributes to the students’ communicative skills development, and (3) the CLI implements a modern Islamic boarding school-based curriculum. The findings also reveal the strategies used by the teacher for improving the students’ speaking skills are presenting grammar and vocabulary materials, conducting communicative activities, learning outside the school, and using English consistently to foster students’ engagement, using code-switching and code-mixing. The students perceive the CLI program is beneficial to increase their English and support their learning. One challenge was also revealed, as the habit of using English in the program affected their proficiency in Bahasa. The study contributes to the body knowledge in foreign language learning